Analisis Kebutuhan Media Pembelajaran Warisan Budaya Berbasis PowerPoint Interaktif (WARPOINT) pada Pembelajaran IPAS Kelas V Sekolah Dasar - Henni Anggraeni Novitasari; Saeful Mizan; Wendri Wiratsiwi (Edukasi Elita : Jurnal Inovasi Pendidikan, 2026)
The availability of teaching media and the existence of learning resources are crucial determinants in supporting the success of the educational process. The implementation of this research is oriented to analyzing the need for interactive PowerPoint based learning devices on the topic of  cultural heritage material to support the learning process. Participation involved in this study consisted of the teacher and 31 fifth grade elementary school students. Date were collected through observation and in depth interviews with related respondents. The research approach implemented in this study adopts qualitative descriptive. Based on the data analysis, it was found that the use of learning media is still limited and not fully interactive. Learning is also still dominated by lecture methods and relies on books as the main guide and reference. The limitations of this phenomenon have implications for students who lack focus, quickly feel bored, and experience difficulties in understanding cultural heritage material. Based on the results of the needs analysis, interactive PowerPoint based learning media can be a solution in learning cultural heritage material to be more interactive, interesting, train students’ critical thingking skills, and help achieve learning objectives optimally.